Comparitive gait analysis for criminal investigation using leave bag behind technique - Zainol, Norfazilah; Mohamad, Kamaruddin Malik (Penerbit UTHM, 2017)
Biometrics has become a very important field of science because of several factors, the growing demand for security in various situations. Some types of biometric identification systems, such as the use of the retina is very accurate. But generally, in order for such a system to identify features that are available on the subject, the subject must enrol voluntarily in a central database to store data to confirm their identity. To identify selected a small group of people with special access privileges, the subject cannot positively identify anyone who is not registered in the system, they can also tell that they are, but not who they are.